Characterization of hatch‐size and growth rates of captive and wild‐reared brown kiwi (Apteryx mantelli) chicks. Issue 5 (9th September 2013) - Prier, Erica A.; Gartrell, Brett D.; Potter, Murray A.; Lopez‐Villalobos, Nicolas; McLennan, John
Abstract Avian growth rate patterns represent a trade off between a tissue's functional maturity and its capacity for growth. At the time of hatch, the brown kiwi (Apteryx mantelli) limb has a high level of maturity in order for the chick to be able to kick its way out of the shell and walk and forage independently from an early age. Growth curves of limb segments, bill length and bodyweight are presented for captive‐reared, BNZ Operation Nest Egg™ chicks over a period of 3 months from the point of hatch. Some parameters were slightly larger in the females than in males at time of hatch, including the bill length. Growth in bodyweight began to slow earlier in males than in females. Regressions of limb and bill measurements over time showed linear patterns of growth instead of a sigmoidal curve as seen in other birds, probably due to the short period of observation. Bodyweight and bill length were then compared to these morphometrics in a wild population of kiwi. Captive‐reared chicks were found to hatch with shorter bills and to increase in bodyweight at a faster rate than the wild birds. Rapid weight gain has been implicated in developmental limb deformities in other precocial and long‐legged birds and should be avoided in captive kiwi. Zoo Biol. 32:541–548, 2013. © 2013 Wiley Periodicals Inc.